Autocorrelation Spatial Infrastruktur Transportasi di Jawa Tengah - Abdul Karim; Muhammad Saifudin Nur; Akhmad Faturohman (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This paper describes the spatial dependence of road transport infrastructure in Central Java using Moran's global approach. The results show that road transport infrastructure in Central Java has a spatial dependence on alpha five percent. In addition, the value of Moran's index is positive which indicates that each adjacent area has a positive spatial dependence.Keywords: spatial autocorrelation, Moran's I, Spatial Dependency, Transportation Infrastructure.